Upregulation of pAKT(Ser473) expression in progression of HPV-positive oropharyngeal squamous cell carcinoma - Horn, Dominik; Freudlsperger, Christian; Kunzmann, Kevin; Plinkert, Peter K.; Dyckhoff, Gerhard; Hoffmann, Jürgen; Freier, Kolja; Heß, Jochen (Head & neck, 2017)
Background: PIK3CA alterations have been shown to be a frequent event in oropharyngeal squamous cell cancer (SCC), especially in human papillomavirus (HPV)-related tumors. Methods: Tissue microarrays (TMAs) were used to evaluate pAKT(Ser473)/(Thr308), total protein kinase B (AKT)(pan) and phosphatase and tensin homolog (PTEN) expression in primary tumors and corresponding nodal disease in oropharyngeal SCC. The HPV status was determined in regard of HPV16 DNA and RNA. Survival analysis was performed by using Kaplan-Meier curves, log-rank testing, and multivariate Cox regression analysis. Results: HPV16 is a prognostic predictive marker for advanced oropharyngeal SCC. pAKT(Ser473) and PTEN are highly expressed in HPV-related oropharyngeal SCCs in contrast to pAKT(Thr308). The pAKT(Ser473) expression increased from primary tumors to progressive nodal disease (21.1%; P < .011). Conclusion: Activation of phosphoinositide 3-kinase (PI3K)/pAKT(Ser473) frequently occurs in advanced HPV-positive oropharyngeal SCC and elevated pAKT(Ser473) levels represent a feature during progression of oropharyngeal SCC, indicating a critical role of the mammalian target of rapamycin (mTOR) complex. Further studies are required to evaluate specific drugs targeting PI3K/AKT/mTOR in consideration of PIK3CA alterations.
Gesehen am 04.09.2018